I'm going to build a supermarket one of these days - Martin, Bill, 1916-; Von Molnar, Barbara; Baten, Helen; Papas, William (New York, Holt, Rinehart and Winston, 1970)
A little boy imagines all the things he will have in the fantastic supermarket he plans to build.
Keywords: Stories in rhyme